Navigating Colonial Orders: Norwegian Entrepreneurship in Africa and Oceania - Kirsten Alsaker Kjerland, Bjørn Enge Bertelsen (Berghahn Books, 2014)
A Norwegian in Africa – in the 1680s? What? Until a decade ago, such questions as well as the exchange of odd stories of a similar sort were the order of the lunchroom day between two Africanists at the University of Bergen. These stories were defi nitely sidetracks for both, whose respective PhD dissertations were concerned with Indian Ocean trade and Sufi sm and the struggle for land in rural colonial Kenya. Curiosity soon gave way, however, to academic obsession, and in October 2002 a popular science anthology about Norwegians in Africa and Africans in Norway was published, entitled Nordmenn i Afrika – afrikanere i Norge (Kjerland and Bang 2002). This anthology focused mainly on Norwegians in Africa, as well as a minor section presenting examples of some unfortunate few Africans stranded in the cold north. We all know the wonderful sound of a positive review – not to mention the euphoria caused by several. To Anne K. Bang’s and my own amazement, however, feedback primarily came in the form of numerous calls, lett ers and emails from accidental readers who had family connections with African histories, who possessed personal archives and photo albums or who wanted to know more about particular people or contexts mentioned in the anthology. In sum, all this led to our conviction that the story of Norwegians in Africa was a thoroughly underresearched area – a piñata calling out for a much more decisive strike, if you will. With this in mind, serious research eff orts were soon focused towards challenging some well-established myths, centred on a handful of questions. Why did a not insignifi cant number of Norwegians head towards Africa at a time when the United States of America was the magnet – a land of milk and honey that became the new home of some eight hundred thousand Norwegians between the 1830s and the 1930s? Who were those few who did not follow the mainstream? What were their motives, where did they end up and what did they do? Few indeed; in 1911 the offi cial number of Norwegians in South Africa (where most went) was some sixteen hundred persons, mainly men. The majority lived in Natal, in and near Durban, where the only Norwegian settlement initiated by a South African government representative was found. In the early 1880s some two hundred Norwegian men, women and children arrived at the same time, on the same boat, in Port Shepstone. They sett led nearby on forty equally sized plots (ca. one hundred acres each) surrounded by Zulu grass huts. Thirty years later some were still there, but at that moment most of the Norwegians (more than one thousand people) lived in Durban itself. A city within the city included a Norwegian church, a Norwegian cultural hall, a Norwegian school, a Norwegian rowing club, a Norwegian choir and a newspaper in the Norwegian language, not to mention the many Norwegian chandlers deeply involved in shipping and trade. Given that the Norwegians in this town had money in their pockets, Norwegian culinary specialities of those days – pultost (a cheese made from soured milk fl avoured with caraway seeds) and akevitt (aquavit) – were easily accessible (Saxe 1914; Semmingsen 1950).